Unpacking Physics Teachers’ Perceptions of Assessment and the Challenges of Classroom Implementation: Insights from Bengkayang District, Indonesia - Duti, Demei; Sirait, Judyanto; Sulaiman, Naim (Jurnal Paedagogy, 2026)
This study aims to analyze physics teachers' perceptions of assessment implementation in learning and to identify the challenges they face in state senior high schools in Bengkayang Subdistrict, Bengkayang Regency, West Kalimantan Province. A qualitative approach was employed through in-depth interviews and document analysis involving four physics teachers selected using purposive sampling. The data were analyzed using thematic analysis through the stages of data condensation, data display, and conclusion drawing and verification. The findings indicate that teachers have implemented various types of assessment, including diagnostic, formative, and summative assessments, through written tests, oral tests, quizzes, and practical activities. The findings also reveal a high level of teacher awareness regarding the importance of assessment in supporting student learning, as reflected in their efforts to integrate assessment throughout the learning process. However, limited instructional time and inadequate laboratory facilities remain the primary challenges to effective assessment implementation. To address these constraints, teachers adopted adaptive strategies, such as continuing assessment activities in subsequent class sessions and utilizing alternative learning media, including PhET Simulations. These findings suggest that the effectiveness of assessment implementation largely depends on teachers' ability to adapt to resource limitations while maintaining the quality of the assessment process.